Evaluation of Vocational Certification Program for Vocational High School Students through Professional Certification Institutions-P1 Ceramic Craft, Textile Craft, and Wood Craft Expertise Competencies - Majid, Juairiah; Harapan, Edi; Nugroho, Heri Setiyo (Yayasan Sembilan Pemuda Indonesia, 2024)
SMK Negeri 2 Kayuagung is the only school in South Sumatra that has a department of creative ceramic crafts, creative textile crafts, and creative wood and rattan crafts located at Kapten Arsyad, Kedaton Village, Kayuagung City District, Ogan Komering Ilir Regency. This school has a professional certification institution, licensed P1 by BNSP, and has implemented a skills certification test program in each study program. The implementation of the Professional Certification program P1 aims to provide Work Competency Certification for students. This Work Competency Certification will affect the educational outcomes of students in the future. The purpose of this study program is to find out how. The implementation of the KKNI level II work competency certification program for the skills competencies of students in creative ceramic crafts, creative textile crafts, and creative wood and rattan crafts. This study program is descriptive qualitative with an evaluation method using the Context, Input, Process, and Product models. The CIPP method focuses on context and includes legal basis, vision, mission, and objectives. The inputs include students, educators, facilities and infrastructure, financing, curriculum, and assessors. The process includes registration, pre-assessment, and assessment, and the product includes reporting of results. The Job Certification Competency Program for Participant Education has a positive impact on participant skills.